THE ROLE OF ENTREPRENEURSHIP EDUCATION IN MODERATING ENTREPRENEURIAL INTENTION AND SELF-DEVELOPMENT IN SOCIAL ENTREPRENEURSHIP AT STUDENTS OF THE UNIVERSITY OF PGRI ADI BUANA - Wibowo, Tony Susilo; Sahrul, Sahrul (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Students as agents of change are a significant part of entrepreneurial activities. Entrepreneurial intention needs to be nurtured from an early age and can create added value for others by implementing social entrepreneurship. This study aims to determine, analyse and prove the influence of entrepreneurial intention, self- development, and social entrepreneurship with entrepreneurship education as a moderating variable. Respondents in this study were 200 students who had attended entrepreneurship education with the instrument using a closed questionnaire. The test results prove that the entrepreneurial interest variable does not affect social entrepreneurship, then the self-development variable has no significant effect on social entrepreneurship. Furthermore, the entrepreneurship education variable acts as a moderating variable that can moderate entrepreneurial intention and self-development towards social entrepreneurship. This is likely to happen because increasing enthusiasm for entrepreneurship takes time and a process. Then entrepreneurship education can foster social sensitivity that can form social entrepreneurship.